1992
DOI: 10.1002/j.1460-2075.1992.tb05474.x
|View full text |Cite
|
Sign up to set email alerts
|

BCS1, a novel gene required for the expression of functional Rieske iron-sulfur protein in Saccharomyces cerevisiae.

Abstract: Respiratory deficient pet mutants of Saccharomyces cerevisiae assigned to complementation group G2 define a new gene, named BCS1, whose product is shown to be necessary for the expression of functional ubiquinol‐cytochrome c reductase (bc1) complex. Immunological assays indicate a gross reduction in the Rieske iron‐sulfur subunit in bcs1 mutants, while other subunits of the ubiquinol‐cytochrome c reductase complex are present at concentrations comparable to the wild type. Transformation of bcs1 mutants with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
120
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(127 citation statements)
references
References 51 publications
7
120
0
Order By: Relevance
“…cerevisiae three homologues, BCS1, MSP1 (YTA4) and YME1 (YTA11), have been identified so far. BCS1 is required for the assembly of the ubiquinol-cytochrome c reductase complex [21]. The MSP1 (YTA4) gene product is an integral protein of the mitochondrial outer membrane and affects intramitochondrial protein sorting [22].…”
Section: Introductionmentioning
confidence: 99%
“…cerevisiae three homologues, BCS1, MSP1 (YTA4) and YME1 (YTA11), have been identified so far. BCS1 is required for the assembly of the ubiquinol-cytochrome c reductase complex [21]. The MSP1 (YTA4) gene product is an integral protein of the mitochondrial outer membrane and affects intramitochondrial protein sorting [22].…”
Section: Introductionmentioning
confidence: 99%
“…Rhodanese (4) and 3-mercaptopyruvate sulfurtransferase (5) were effective in purified in vitro systems, comprising apoprotein, thiol, ferrous ion, and the respective sulfur-containing substrate, thiosulfate, or mercaptopyruvate. Analysis of yeast respiration-deficient mutants suggested a role for the BCS1 gene product (6) in the synthesis of functional Rieske protein. Studies on nif mutants of Azotobacter vinelandii (7) identified nifS as essential for nitrogenase activity.…”
mentioning
confidence: 99%
“…In addition it has been found (Tzagoloff and Dieckmann, 1990) that there are additional proteins that are needed for the proper functional assembly of these heteromeric membrane enzymes but these proteins are not part of the isolated biochemically active enzymes. These extra-enzyme activity factors are thought to be 'assembly facilitators' or specialized chaperones but the molecular mechanism of their action is usually unknown, although their inactivation generates clear respiratory deficient phenotypes (Nobrega et al, 1992;Souza et al, 2000). This class is mostly dispersed among NADH-cytochrome c reductase, cytochrome oxidase and general respiratory ability categories (Table III).…”
Section: Discussionmentioning
confidence: 99%